2023
DOI: 10.1101/2023.03.14.532526
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Step-wise mechanical unfolding and dissociation of the GAIN domains of ADGRG1/GPR56, ADGRL1/Latrophilin-1 and ADGRB3/BAI3: insights into the mechanical activation hypothesis of adhesion G protein-coupled receptors

Abstract: Adhesion G protein-coupled receptors (aGPCRs) are a large family within the superfamily of G protein-coupled receptors involved in various physiological processes. One unique feature of aGPCRs is their long N-terminal extracellular regions (ECRs), which contain adhesive domains and a GPCR autoproteolysis-inducing (GAIN) domain. This GAIN domain promotes autoproteolytic cleavage of aGPCRs into N- and C-terminal fragments (NTF, CTF, respectively) after receptor biosynthesis. aGPCR signaling involves an interplay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
1
0
0
Order By: Relevance
“…Our data are consistent with a recent study by Fu et al in which the authors observed unfolding transitions of ∼15–20 nm at forces in the 5–10 pN range for the GAIN domains of GPR56, Lphn1, and BAI3 using a magnetic tweezers assay . Our observation of ∼13 nm steps between 4 and 5 pN therefore agrees well with the structural transitions observed in other GAIN domains, particularly when taking into account the differences between the equilibrium force measurements in this study and the force ramp experiments used by Fu et al The experiments reported by Fu et al likewise indicate that a reversible structural transition precedes dissociation for GPR56 and Lphn1 . These complementary studies thus suggest that mechanical force is likely to activate aGPCRs via a mechanism that is broadly conserved.…”
supporting
confidence: 93%
“…Our data are consistent with a recent study by Fu et al in which the authors observed unfolding transitions of ∼15–20 nm at forces in the 5–10 pN range for the GAIN domains of GPR56, Lphn1, and BAI3 using a magnetic tweezers assay . Our observation of ∼13 nm steps between 4 and 5 pN therefore agrees well with the structural transitions observed in other GAIN domains, particularly when taking into account the differences between the equilibrium force measurements in this study and the force ramp experiments used by Fu et al The experiments reported by Fu et al likewise indicate that a reversible structural transition precedes dissociation for GPR56 and Lphn1 . These complementary studies thus suggest that mechanical force is likely to activate aGPCRs via a mechanism that is broadly conserved.…”
supporting
confidence: 93%